Sporotrichoid lupus vulgaris: A rare presentation - Maheshwari, Anshul (Indian Dermatol Online J, 2015)
Lupus vulgaris is the most common presentation of cutaneous tuberculosis in India and can present as papular, nodular, plaque, ulcerative, vegetating, and tumid forms. Unusual variants include the frambesiform, gangrenous, ulcerovegetating, lichen simplex chronicus, myxomatous, and sporotrichoid types. We describe a rare sporotrichoid presentation of lupus vulgaris on the leg of a 28-year-old female of 12 years duration.